أحاديث الأطعمة والأشربة ومدى تطبيقاتها في الأغذية الحلال الماليزية (JAKIM) - Yasir Ramlee (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2014)
This research discusses the ahadith on food and beverages and the extent of their application in Malaysian Halal Food (JAKIM). It attempts to explain the actual understanding of food and beverages in Islam and its principles. Furthermore, the research describes the Prophet's sallallahu 'alayhi wasallam manners on food consumption from the sunnah perspective, and discusses the roles of al-ahadith al-nabawiyyah in Malaysian Halal Food. In order to examine the application of ahadith in Malaysian Halal Food, the researcher studied certain topics in the syllabus; among which are slaughtering, intoxicants, greases, gelatins and contaminations. For the study, researcher used three methods. Using the induction method, the researcher collected and categorized the al- ahadith related to food and beverages mentioned in main sources of hadith. Secondly, the researcher analyzed the collected ahadith and the views of scholars related to the ahādīth to extract from them the rules, wisdom, and benefits. Finally, comparison between al-nusus al- ahadithiyyah and the opinions of experts was made to see if it can be implemented accordingly in Malaysian Halal Food. Through the study, it is confirmed that Malaysian Halal Food (JAKIM) applied al- ahādīth al-nabawiyyah related to food and beverages in its syllabus.